Early detection of cerebrospinal fluid/serum glucose ratio: A promising value for mortality prognosis in patients with acute bacterial meningitis - Nasrin Khodashenas; Rouzbeh Rajaei Ghafouri; Asghar Jafari Rouhi; Moloud Balafar (Journal of General and Family Medicine)
Abstract Background/Aims Given that acute bacterial meningitis (ABM), as community‐acquired meningitis, is considered a life‐threatening medical emergency, early diagnosis and immediate onset of antibiotic therapy are of great importance. Here, we aimed to compare both the laboratory and glucometer assessment of cerebrospinal fluid (CSF)/serum glucose ratio in patients with suspected ABM. In addition, the prognostic value of the CSF/serum glucose ratio on the mortality rate was also evaluated. Methods In this cross‐sectional, single‐center study, all demographic and clinical characteristics of patients who attended the emergency department were evaluated. A total of 200 patients with clinical suspicion of ABM underwent lumbar puncture (LP) and were simultaneously recruited for CSF and serum glucose measurement using both laboratory tests and a point‐of‐care glucometer device. Data analysis was performed using SPSS ver. 20.0. Results Out of 200 suspected subjects with a mean age of 52.66 ± 6.64 years (male = 113, 56.5%), 23 patients (11.5%) were identified with confirmed ABM. The study findings showed a close correlation between the laboratory and glucometer‐measured CSF/serum glucose ratio. The sensitivity and specificity of the glucose ratio measured by the laboratory test were 91.3% and 86.4%, respectively. A similar result was also observed by glucometer measurement (Sensitivity: 91.3%, Specificity: 89.3%, p < 0.001). However, the mean time needed for CSF glucose measurement was significantly longer in the laboratory method compared to the glucometer‐based assessment (p < 0.0001). Notably, the CSF/serum glucose ratio was considerably lower in deceased patients (n = 9, p < 0.05). Conclusion Despite the similar accuracy of the CSF/serum glucose ratio using either a laboratory test or glucometer for ABM diagnosis, the present study highlighted that the laboratory turnaround time was significantly improved using a glucometer, which could be considered a reliable aid to the prognosis of mortality.